Transforming management in Central and Eastern Europe - Martin, Roderick (Oxford University Press, 1999)
This study provides an analysis and comparison of changes in enterprises in seven European transitional economies since 1989. It argues that these countries are developing a distinctive hybrid form of politicized managerial capitalism.